Islamic and international humanitarian law on rape during armed conflict: A comparative analysis - Qanet, Ghulam Mohammad; Eishan Jan, Mohammad Naqib; Mohammad, Mohammad Tahir Sabit; Ahmad, Muhamad Hassan (Serials Publications Pvt. Ltd., 2020)
Since time immemorial, rape has been a regular practice in all kinds of wars waged throughout the world. Sometimes, it is deliberately practice as a tactic of war to demoralise the enemy nation’s population as a whole. So far, such practice during armed conflict has been outlawed under both Islamic and International Humanitarian Law (IHL). Nevertheless, this does not stop combatants of all backgrounds from committing rape in armed conflict. Accordingly, this paper aims at comparatively analysing the legal position of rape during armed conflict from both Islamic and IHL perspectives.